BRING BACK OUR FUTURE! THE CREATIVE POTENTIAL OF NOSTALGIA IN ALEKSANDER HEMON’S JOURNALISTIC WRITINGS - Giergiel, Sabina (Porównania, 2014)
With reference to the feature articles of a Bosnian prose-writer, Aleksander Hemon, the authoress depicts active, yet not sentimental, creative potential of nostalgia that is directed towards the future (and not the past). Hemon’s voice in the matter is turned against the actual state of affairs i.e. the reality of divided Bosnia and Herzegovina. However, the traditional values, once present in Yugoslavia, can ensure a better future for the novelist’s homeland. These values pertain to the community, which facilitates mutual exchange of thoughts and ensures the sense of belonging to a heterogeneous community, as well as hope, which is based on the belief that the future is in the hands of the community and that tomorrow can be better than today.